The geometrical tolerancing desk reference creating and interpreting ISO standard technical drawings - Green, Paul, I.Eng (Elsevier/Newnes, 2005)
The complete day-to-day guide to geometrical tolerancing and technical drawings, design and specification of components.
Includes index.
Keywords: Tolerance (Engineering); Mechanical drawing.; elektronické knihy; electronic books